The significance of personal value, risk attitude and trust on life insurance ownership in the northern regions of Malaysia - Lim, Chee Chee; Tan, Suang Sin (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper examines the relationships of life insurance ownership with personal value, risk attitude and trust among the individuals in the northern regions of Malaysia to enable the undertaking of appropriate actions in promoting life insurance ownership by individuals (residing in the northern regions of Malaysia) who have not owned life insurance yet. A structured questionnaire was used to collect data. Stratified random sampling method was used to approach respondents. The data were subject to binary logistic regression analysis. The major finding shows that only trust is found to have a (positive and) significant relationship with life insurance ownership. Thus, this paper proposes that life insurance agents are required to undergo professional trainings in life insurance selling to minimize the incidents of misconducts among agents. This can promote a greater trust among the prospects in agents and increase the likelihood of owning life insurance. In addition, directions for future research are also highlighted.